2012
DOI: 10.1007/s00453-011-9611-5
|View full text |Cite
|
Sign up to set email alerts
|

Computing Without Communicating: Ring Exploration by Asynchronous Oblivious Robots

Abstract: Abstract. We consider the problem of exploring an anonymous unoriented ring by a team of k identical, oblivious, asynchronous mobile robots that can view the environment but cannot communicate. This weak scenario is standard when the spatial universe in which the robots operate is the two-dimentional plane, but (with one exception) has not been investigated before. We indeed show that, although the lack of these capabilities renders the problems considerably more difficult, ring exploration is still possible. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
79
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(80 citation statements)
references
References 39 publications
1
79
0
Order By: Relevance
“…This task is challenging because the ring is unoriented and the agents cannot ''remember'' the direction of their last move (otherwise, they could simply continue forward). Considering deterministic algorithms, Flocchini et al [11] have shown that the problem is unsolvable if n and k are co-prime. They have also provided an algorithm which solves the problem otherwise.…”
Section: Related Workmentioning
confidence: 99%
“…This task is challenging because the ring is unoriented and the agents cannot ''remember'' the direction of their last move (otherwise, they could simply continue forward). Considering deterministic algorithms, Flocchini et al [11] have shown that the problem is unsolvable if n and k are co-prime. They have also provided an algorithm which solves the problem otherwise.…”
Section: Related Workmentioning
confidence: 99%
“…As mentioned previously, our scenario for the graph world has been previously used in [17,18] in the context of gathering and in [12,13] in the context of exploration. Proof.…”
Section: Related Workmentioning
confidence: 99%
“…In [17,18] the related problem of gathering was investigated on a ring: robots starting from different locations have to meet in one node. In [12,13] the focus was on exploration, as in the present paper. In [12] the authors investigated the sizes of teams of robots capable of exploring trees: it was proved that there are n-node trees of maximum degree 4 where Ω(n) robots are necessary for exploration and that all trees of maximum degree 3 can be explored by O ( log n log log n ) robots.…”
mentioning
confidence: 97%
See 2 more Smart Citations